Gender Violence, Enforcement, and Human Capital : Evidence from Women's Justice Centers in Peru - Sviatschi, Maria Micaela (World Bank, Washington, DC, 2021)
In many developing countries, access to justice remains unequal, especially for women. What are the implications of this inequality for gender-based violence and investment in children? This paper provides evidence from Peru’s women’s justice centers (WJCs), which are specialized institutions that provide police, medical, and legal services to reduce gender-based violence. Examining the gradual rollout of WJCs across districts and villages, the study finds that the opening of a center reduces the incidence of gender-based violence, as measured by domestic violence, female deaths due to aggression, and hospitalizations due to mental health, by about 10 percent. This decrease in women’s exposure to violence has intergenerational effects: WJCs substantially increase human capital investments in children, raising enrollment, attendance, and test scores. The evidence suggests that these results are driven by an increase in enforcement against gender violence. After a WJC opens, there is an increase in reporting and prosecutions of gender-specific crimes.